ANALISIS RASIO PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN DALM MEMPREDIKSI PERINGKAT OBLIGASI (Studi Pada Perusahaan Non Keuangan dan Non Perbankan di Bursa Efek Indonesia Periode 2009-2014) - Retno Dwi Krisnawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Bond is one of instruments in which investors interest a lot due to its fixed revenue; meanwhile, issuers see bonds as a safe investment because of its lower cost. This trend raises the value of outstanding bonds. In 2007, for example, the value increased very significantly. Regardless the fact of the value decline in 2008 as the inevitable effect of global financial crisis, corporation bonds successfully regained their precious value in the following year. However, bonds are still risky of such payment failure that a prospective investor should carefully consider the bond ratings because they can predict the future risk level. The research tries to examine the extent to which profitability ratio, liquidity, leverage, and company size influence the predictability of bond ratings. The companies running non-financial and non-banking businesses owning bonds during 2009-2014 are taken as the samples of the study. Population on this study as many as 17 companies, after used purposive sampling then obtained as many as 7 sample companies. The data are analyzed through logistic regression model. The results of the study show that profitability ratio and leverage variables do not significantly influence the bond rating, while the other variables give significant effect toward the rating.Keywords: Bond rate; Profitability; Liquidity; Leverage; Company Size